2019
DOI: 10.1021/acs.iecr.9b02272
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic-Polymer-Assisted Hot Water Flooding toward Viscous Oil Mobilization

Abstract: Heavy oil recovery is the most challenging part for the petroleum industry, and several techniques including steam and water injection are currently used that are either energy intensive, expensive, or less efficient. This study aims to evaluate a novel amphiphilic viscosity reducing polymer (DN-1) used along with hot water flooding for promoting viscous oil mobilization. Its performance for heavy oil mobilization was evaluated using viscosity measurements at different temperatures followed by core flooding ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The plateau zone indicates the micelle formation, and the break point reported in the surface tension curve is said to be the cmc. The observed data reveal that, on enhancing the alkyl chain length, there is a decline in the cmc value. This decrease is associated with the increased hydrophobic interactions among the long chain alkyls. The surface parameters of BG6 and BG12 are given in Table .…”
Section: Resultsmentioning
confidence: 92%
“…The plateau zone indicates the micelle formation, and the break point reported in the surface tension curve is said to be the cmc. The observed data reveal that, on enhancing the alkyl chain length, there is a decline in the cmc value. This decrease is associated with the increased hydrophobic interactions among the long chain alkyls. The surface parameters of BG6 and BG12 are given in Table .…”
Section: Resultsmentioning
confidence: 92%
“…Polymeric surfactant forms a stable oil in water emulsion, reducing the viscosity of crude oil; the low IFT between polymeric surfactant and heavy oil can obtain a higher capillary number and lower residual oil saturation. A Hassler-type core holder was used to carry out heavy oil hot water flooding, as well as an epoxy resin bonded core with a diameter of 4.5 cm × 4.5 cm × 30 cm; moreover, a relative permeability to water of 1080 mD, a porosity of 26.08%, and an initial oil saturation of 70.7% were used, as shown in Figure . As shown in Figure , oil recovery of 50 °C low-salinity (LS) water flooding is 62.16% OOIP, LS-hot water flooding at 110 °C is increased by 4.87% OOIP, and SB-polymer-assisted hot water flooding and posthot water flooding at 110 °C is 19.46% OOIP.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature on the heavy-oil viscosity reduction in the past years, ,,, polyacrylamide (PAM) was chosen as the skeleton modified with different groups to analyze the effect both horizontally and vertically. The molecular structures of the nine fragments are shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was found that emulsification viscosity reducers mostly focus on amphiphilic polymers, , which have both hydrophilic and lipophilic groups, also called surfactants. We designed the amphiphilic polymer to reduce the oil viscosity based on two points: one is to form the O/W emulsion and the other is to break the strong interaction among aromatic rings, which is mainly governed by the π–π effects.…”
Section: Introductionmentioning
confidence: 99%